The Factors Influencing the Level of Well-being among Elderly in Selangor - Osman, Umi Abidah Noor; Ismail, Ramlee (Management Research Journal, 2018)
The increasing in ageing population has drawn on the attention to the level of well-being among elderly. This study measured the level of well-being among elderly in Selangor. It was study conducted to determine how far factors such as personal factor, social participation, financial factor, neighborhood and the level of income influencing the well-being. A survey method was conducted to collect data using a total sample of 466 respondents living in rural and urban areas. In order to access the statistical significant differences between these two living areas on the well-being among elderly in Selangor, t-test analysis was used. In addition, multiple regression analysis was performed to measure the influence of the relevant factors to the elders’ level of well-being. The findings showed that all the factors had influenced the level of prosperity among elderly. However, income factor was not an essential factor in the welfare of old people. Therefore, the implication of this study suggested that the elderly must be provided with their personal and social needs to increase their level of well-being.